Identification of promising high yielding blast resistant rice genotype for hilly conditions of Karnataka - Hosagoudar, GN; ., Sheshaiah (ORYZA-An International Journal of Rice, 2019)
Rice (Oryza sativa L.) is one of the most important food crops from which nearly one third of world's population derives its principal source of calories. The experiment was conducted to discover the impending genotypes suitable for hilly situation of Karnataka. The experimental materials were chosen or selected based on significant superiority or on par yield over the local check variety, i.e., Tunga in the AICRIP investigational trials of paddy. The chosen entries were evaluated for the three years in the station trial at the Agricultural and Horticultural Research Station, Ponnampet in randomized complete block design with two replications during 2016, 2017 and 2018 kharif seasons. Third year Multi Location Trial (MLT) was also conducted at AHRS, Ponnampet andZAHRS, Mudigere. The pooled data across the years in the station trial revealed that the entry IET-24451 recorded the utmost grain yield (6196 kg/ha) among the entries and gave up 36 per cent increased grain yield over the Tunga and 17 per cent increased grain yield over the KPR-1. The pooled data of MLT across thelocations revealed that the entry IET-25281 recorded the utmost grain yield of 6076 kg/ha with 11 per cent increased grain yield over the Tunga and 13 per cent increased grain yield over the KPR-1. The combined pooled data of station trial across the years and MLT trial across locations revealed that the entry, IET-24451 of 6135 kg/ha recorded the maximum grain yield followed by IET-25281 (5970 kg/ha) among the entries. The entry IET-24451 recorded 22 per cent increased grain yield over the Tunga and 15 per cent increased grain yield over the KPR-1, whereas the entry IET-25281 recorded 19 per cent increased grain yield over the Tunga and 12 per cent increased grain yield over the KPR-1 and both the entries IET-24451 and IET-25281 recorded the leaf and neck blast resistance reaction in the Uniform Blast Nursery Screening Pattern. Hence, the entry IET-24451 was recommended for on-farm trial due to its blast resistance trait and yield superiority across the yearsand the locations.